2014
DOI: 10.17221/4/2014-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Impact of risk factor management on the sanitary condition of Norway spruce (Picea abies [L.] Karst.) pure stands in Latvia

Abstract: ABSTRACT:In management of young forest stands, it is often the case in forestry that several risk factors, biotic, abiotic and anthropogenic ones, have to be dealt with. An anthropogenic factor is of great importance in management of forests, because humans, using ecosystems for their needs, still have to maintain the spatial structure of the forest and prevent the worsening of the health state. Covering all territory of Latvia, empirical material was gathered in 25 pure stands. To find out how neighbouring st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
1
3
0
Order By: Relevance
“…The most commonly observed stands damage caused by hoofed animals was stem bark scratches and broken tree branches. Evaluating ungulates risk factors, the study conducted showed that ungulates killed more formations located near the clearing, but among adults stands damage was less, which coincides with previous studies (Ruba and Miezīte, 2014).…”
Section: Impact Of Young Forest Stand Density and Health Status On Hesupporting
confidence: 87%
“…The most commonly observed stands damage caused by hoofed animals was stem bark scratches and broken tree branches. Evaluating ungulates risk factors, the study conducted showed that ungulates killed more formations located near the clearing, but among adults stands damage was less, which coincides with previous studies (Ruba and Miezīte, 2014).…”
Section: Impact Of Young Forest Stand Density and Health Status On Hesupporting
confidence: 87%
“…and anthropocentric one. An essential role for the carrying out of these fellings is damage caused by cervids game whose impact is essential (Rūba, Miezīte, & Luguza, 2014;Šņepsts et al, 2018), and wind resulting in significant natural disturbances (Donis et al, 2020;Snepsts et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%
“…Forest road network is one ecosystem, which is managed by a human, and it can positively or adversely affect the stands next to the existing plants and trees (Demir, 2007), therefore is important to assess the magnitude of the anthropogenic impact on this ecosystem (Gadow et al, 2013). Irregular, naturally created shaped areas transformation into a regular and incorrectly performed thinning can lead to a deterioration of the health status in the young stands, causing a variety of diseases and insect invasion (Ruba et al, 2014). The aim of the research was to analyze impact of forest plots spatial structure on management of Norway spruce young forest stands).…”
Section: Introductionmentioning
confidence: 99%